Socializing Religious Moderation and Peace in the Indonesian Landscape - Paelani Setia; Mohammad Taufiq Rahman (Jurnal Iman dan Spiritualitas, 2022)
This paper discusses the idea of religious moderation addressed for peace in Indonesia. This paper is a library research through reference sources on the concepts of religious moderation and peace circulating in Indonesia's new tradition of literacy. This paper concludes that the Indonesian people who have religious diversity need visions and solutions that can build harmony and peace in religious life, especially by using religious moderation to accept different views, and without falling into intolerance, radicalism, and extremism. The goal of religious moderation is to find a middle ground between the two extremes of religion, and to do so peacefully. On the one hand, there are religious fundamentalists who insist that only one religious scripture reading is correct and view all those who disagree as heretics or even infidels. This ultra-conservative group is still reasonably influential, especially in urban areas.